Kontribusi Madu Lebah Hutan Terhadap Total Pendapatan Rumah Tangga Petani (Studi Kasus di Desa Loli Kecamatan Polen Kabupaten Timor Tengah Selatan) - Yuyun Rivanti Liunokas; Roni Haposan Sipayung; Lusia Sulo Marimpan; Norman P. L. B. Riwu Kaho (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2025)
Honey from forest bees (Apis dorsata) is one of the non-timber forest products that has long been used in Loli Village, Polen Districk, South Central Timor Regency and has become an additional source of livelihood to meet the needs of farmers in Loli Village. This research aims to determined the contribution of forest honey to farmers' total income and to determine the level of welfare of farmers in Loli Village. This research was carried out during April-May 2024, using saturated sampling method (census), of a total of 19 honey farmers and data analysis using quantitative descriptive analysis. The research results shows that the contribution of forest honey bee farming to the total income of farmer households in Loli Village is 76% with total honey farming income of IDR 372,360,000/year, an average of IDR 19,597,895/year. The results of the analysis proved that of the 19 respondents, only 7 respondents had incomes above the average, while the other 12 respondents had incomes below the average. This is influenced by the large number of trees owned by each respondent and the number of hives in the nesting trees, so it can be ascertained that the gains in honey production are also different. Based on the level of farmer welfare, there are still 74% of honey farmers who are not prosperous, but honey farming is able to provide a good life and is the main support for the welfare of farmers in Loli Village. However this contribution can be threatened if forest preservation is not maintained, so there needs to be a role Government and Community in efforts to protect and preserve forests in Loli Village. Keywords: Forest Honey Bee; Income; Contribution; Welfare Level